Deskripsi Stres Kerja pada Perawat Rawat Inap berdasarkan Faktor Individu menggunakan NIOSH Job Stress Questionnaire di RSUP Dr. Sitanala Tahun 2025 - Helda Zerlyfera; Dwi Nurmawaty; Ade Heryana; Rini Handayani (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Work stress is a prevalent and complex phenomenon frequently encountered by inpatient nurses as a result of the intense physical, emotional, and psychological demands inherent in their professional responsibilities. Nurses are required to deliver high-quality care under conditions of time pressure, emotional strain, and patient diversity, which can increase their susceptibility to stress. Individual factors—including age, gender, marital status, years of service, personality type, and self-assessment—play a crucial role in shaping nurses’ capacity to adapt to these pressures and maintain their performance. This study aims to comprehensively describe the influence of individual factors on work stress among inpatient nurses at RSUP Dr. Sitanala in 2025. Employing a quantitative descriptive design with a cross-sectional approach, a total of 34 inpatient nurses were recruited using total sampling. Data were collected using the NIOSH Job Stress Questionnaire, which measures multiple aspects of job-related stress. The results indicate that younger nurses, those with shorter work tenure, and individuals exhibiting type A personality traits are more vulnerable to experiencing high levels of stress compared to their counterparts. These findings underscore that individual characteristics significantly contribute to variations in work stress levels. The study emphasizes the importance of developing responsive human resource management strategies, such as stress management training, mentoring, and supportive work environments, to strengthen resilience and improve nurses’ well-being. By identifying and addressing these individual factors, healthcare organizations can enhance employee retention, promote patient safety, and ensure sustainable quality of care.